Tenotomia do músculo flexor digital superficial e desmotomia acessória em equinos: goniometria radiometacarpiana, metacarpofalângica e interfalângica - Hussni, Carlos Alberto [UNESP]; Watanabe, Marcos Jun [UNESP]; Alves, Ana Liz Garcia [UNESP]; Nicoletti, José Luiz de Mello [UNESP]; Vulcano, Luiz Carlos [UNESP] (FapUNIFESP (SciELO), 2010)
The purpose of this study was to investigate the effects of the superficial digital tenotomy and the superior check ligament desmotomy on the radio-metacarpal, metacarpophalangeal, proximal and distal interphalangeal angles in horses. Under general anesthesia the superficial digital flexor tenotomy and superior check ligament desmotomy were performed, respectively, on the right and left forelimbs in nine horses. Before surgery and on 15th, 30th, and 60th postoperative days the radio-metacarpal, metacarpophalangeal, and proximal and distal interphalangeal angles were measured by radiographic examination. Tenotomy decreased significantly the metacarpophalangeal angle (mean ± standard deviation: preoperative – 140.7º ± 6.85; 60th day – 128.2º ± 5.93) and increased the distal interphalangeal angle (mean ± standard deviation: preoperative – 172.6 ± 1.87; 60th day – 167.6 ± 1.36). Desmotomy decreased the proximal interphalangeal angle (mean ± standard deviation: preoperative – 180.2º ± 5.43; 60th day- 197.3º ± 8.29). These surgical procedures did not change the radio-metacarpal angle. The superficial digital flexor tenotomy and the superior check ligament desmotomy cause different and significant changes in joint angles distal to the carpus.

A proposta deste estudo foi avaliar os efeitos da tenotomia do músculo flexor digital superficial e a desmotomia do seu ligamento acessório sobre os ângulos formados pelas faces dorsais radiometacarpiano, metacarpofalângico e interfalângicos proximal e distal em equinos. Realizaram-se em nove equinos a tenotomia do músculo flexor digital superficial no membro torácico direito (MTD) e a desmotomia de seu ligamento acessório no membro torácico esquerdo (MTE). A goniometria radiológica foi procedida no pré-operatório e aos quinze, trinta e sessenta dias após as cirurgias. A tenotomia praticada no MTD diminuiu significativamente o ângulo metacarpofalângico (média com desvio-padrão pré-operatório – 140,7 ± 6,85; sessenta dias – 128,2º ± 5,93) e aumentou o interfalângico distal (média com desvio-padrão pré- operatório – 180,2º ± 5,43; sessenta dias – 197,3º ± 8,29). A desmotomia realizada no MTE diminuiu significativamente o ângulo interfalângico proximal (média com desvio-padrão pré-operatório – 172,6 ± 1,87; sessenta dias – 167,6 ± 1,36). As cirurgias estudadas não interferiram nos eixos radiometacarpianos. Os procedimentos cirúrgicos estudados alteraram significativamente os ângulos articulares distais ao carpo.
Superficial digital flexor tenotomy and superior check ligament desmotomy in horses: radiometarcarpal, metacarpophalangeal and interphalangeal goniometry
Keywords: Desmotomy; Horses; Joint angles; Tenotomy; Ângulos articulares; Desmotomia; Equinos; Tenotomia